Analisis Financial Distress Pada Perusahaan Subsektor Restoran, Hotel, Dan Pariwisata Di BEI - Ella Dwi Cahyani; Slamet Riyadi (JURNAL RISET MANAJEMEN (JURMA), 2023)
The “Covid-19” pandemic that occurred from 2019-2022 had an impact on the restaurant, hotel and tourism sub-sector businesses, resulting in a loss of revenue. Early warning of bankruptcy can be obtained by conducting a bankruptcy analysis. The goal of this research is to find out how likely it is that businesses in the tourism, hotel, and restaurant subsector will be in financial distress between 2017-2021 period using the Altman model, internal growth rate, and Springate and to determine the most appropriate and accurate model among the three models. The quantitative descriptive analysis method is used in this study. The population used is the restaurant, hotel and tourism sub-sector companies listed on the IDX. Sampling using purposive sampling method. The analysis tool uses Altman model analysis, internal growth rate, and Springate, as well as testing the level of accuracy. This study's findings show that the Altman model, the internal growth rate model, and the Springate model can predict financial distress in restaurant, hotel and tourism subsector companies listed on the IDX for the 2017-2021 period, and the most accurate model is the Altman model with a high degree of accuracy. the highest was 77.1% and the type error was 22.9%.